SOSIALISASI DAN PENDAMPINGAN PENULISAN ARTIKEL ILMIAH BAGI GURU SMK N 2 BANYUMAS - Yulianita, Nadia Gitya; Yulianti, Uki Hares; Sudaryanto, Memet (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
The community service activities carried out at SMK N 2 Banyumas aim to provide academic writingtraining in order to improve the teachers’ competence at the school. This community service’s themeis a request from teachers in that school who wanted to improve their ability to write scientificpapers. In addition, the results of observations show that the publication of scientific works byteachers of SMK N 2 Banyumas are still lacking. Only a few teachers at SMK N 2 Banyumas havepublished their research results in scientific journals. The methods used in this activity are lectures,discussions, and mentoring. Lectures and discussions are held to present material regardingacademic writing. In addition, knowledge about translating abstracts will also be given because itis part of writing scientific papers. After that, the teachers practice writing scientific papers to bepublished in journals. The results of this community service activities are expected that teachers atthat school will have additional competence in writing scientific papers by applying the theory ofacademic writing.